Specification of sensory neurons occurs through diverse developmental programs functioning in the brain and spinal cord. Issue 11 (18th September 2014) - Dyer, Carlene; Linker, Claudia; Graham, Anthony; Knight, Robert
<x xml:space="preserve">Abstract</x> Background: Vertebrates possess two populations of sensory neurons located within the central nervous system: Rohon‐Beard (RB) and mesencephalic trigeminal nucleus (MTN) neurons. RB neurons are transient spinal cord neurons whilst MTN neurons are the proprioceptive cells that innervate the jaw muscles. It has been suggested that MTN and RB neurons share similarities and may have a common developmental program, but it is unclear how similar or different their development is. Results: We have dissected RB and MTN neuronal specification in zebrafish. We find that RB and MTN neurons express a core set of genes indicative of sensory neurons, but find these are also expressed by adjacent diencephalic neurons. Unlike RB neurons, our evidence argues against a role for the neural crest during MTN development. We additionally find that neurogenin1 function is dispensable for MTN differentiation, unlike RB cells and all other sensory neurons. Finally, we demonstrate that, although Notch signalling is involved in RB development, it is not involved in the generation of MTN cells. Conclusions: Our work reveals fundamental differences between the development of MTN and RB neurons and suggests that these populations are non‐homologous and thus have distinct developmental and, probably, evolutionary origins. Developmental Dynamics 243:1429–1439, 2014. © 2014 Wiley Periodicals, Inc.